The APTAS student CubeSat Mission: A case study for reflective practitioner in education and student teams - Hestad, Theresia; Barabash, Victoria; Laufer, René (Advances in Space Research, 2023)
Despite the growing number of educational CubeSat projects, there is a lack of available literature related to analysis of good practices and lessons learned associated with learning environment of such university student projects, their internal organisational, and management issues. Difficulties arise when international standards, procedures and practices from professional satellite development projects must be adopted by student teams to their local projects. This paper discusses educational, organisational, and human factors that contribute to the success of the master student space projects at Luleå University of Technology, Kiruna Space Campus. The authors focus on project structure, management, working, and learning environment of the ongoing student CubeSat project APTAS and analyse problems and difficulties encountered in relation to the other actual student space projects at LTU. The result of quantitative and qualitative analysis of questionnaires, interviews, reflections and observations of the national and international master students is presented, and provides practical advice for university student teams and their supervisors. Validerad;2023;Nivå 2;2023-08-07 (hanlid)